The relationship between the characteristics of seagrass beds as a macro-rubbish trap in Balikpapan Bay, East Kalimantan - Rasman, Rasman; Sari, Lily Inderia; Irawan, Aditya (Faculty of Fisheries and Marine Science, Mulawarman University, 2024)
Balikpapan Bay is a waters that become sea transportation used by the community and also companies. Community and company activities that use sea transportation cause a lot of garbage in the waters of Balikpapan Bay Seagrass beds are stretches of seagrass vegetation that cover a coastal area or shallow sea. seagrass Balikpapan Bay, East Kalimantan. Data collection using to quadrant transect sampling. Analysis of the data used to determine the relationship between macro-rubbish and seagrass types of rubbish, rubbish volume and seagrass stands. Sampling was carried out using a 50 x 50 cm transect at 4 stations with 3 repetitions. The results of the study found 2 types of seagrass, namely E. acoroides and T. hemprichii. Then 2 types of waste were found, namely organic and inorganic waste Based on the results of the correlation test between macro-rubbish volume and trash seagrass stands, it stated that there was no positive correlation in seagrass beds in the waters of Balikpapan Bay, East Kalimantan.